Mean platelet volume and platelet distribution width in vascular dementia and Alzheimer's disease. (September 2014) - Liang, Qing-Cheng; Jin, Di; Li, Ying; Wang, Rui-Tao
Abstract Activated platelets play a substantial role in Alzheimer's disease (AD) and atherothrombosis. Mean platelet volume (MPV) is an early marker of platelet activation, which is linked to a variety of pro-thrombotic and pro-inflammatory diseases. This study is to examine the association between platelet indices and vascular dementia (VaD) and AD. In this cross-sectional study, we investigated the levels of platelet count, MPV, and platelet distribution width (PDW) in 150 VaD patients, 110 AD patients, and 150 non-demented controls. MPV and PDW were significantly lower in patients with VaD and AD as compared with controls. The decrease in PDW for AD patients as compared with VaD patients was also significant (p < 0.001). In addition, there was a positive correlation between Mini-Mental State Examination (MMSE) and MPV and PDW, after adjusting confounding factors (r = 0.532 for MPV and r = 0.425 for PDW, p < 0.001 for both). Multivariate regression analysis showed that MPV and PDW were significantly associated with MMSE (β = 0.366 for MPV and β = 0.273 for PDW, p < 0.001 for both). In conclusion, MPV and PDW were both decreased in VaD and AD. PDW levels were significantly lower in AD as compared to those in VaD. Our findings suggest that PDW in combination with MMSE scores could be potential indicators for distinguishing VaD from AD.